2019
DOI: 10.1186/s12931-019-1115-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crystalloid, hyper-oncotic albumin, and iso-oncotic albumin on lung and kidney damage in experimental acute lung injury

Abstract: Background Conflicting data have reported beneficial effects of crystalloids, hyper-oncotic albumin (20%ALB), and iso-oncotic albumin (5%ALB) in critically ill patients. Although hyper-oncotic albumin may minimize lung injury, recent studies have shown that human albumin may lead to kidney damage proportional to albumin concentration. In this context, we compared the effects of Ringer’s lactate (RL), 20%ALB, and 5%ALB, all titrated according to similar hemodynamic goals, on pulmonary function, lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…Starch macromolecule accumulation also impairs glomerular filtration and is associated with a higher risk of acute renal failure than gelatin [ 7 ]; however, gelatin is associated with a higher incidence of anaphylactic shock [ 8 , 9 ]. Compared to iso-oncotic albumin, hyperoncotic albumin leads to a higher osmotic pressure, which may alter intraglomerular oncotic force and osmotic nephrosis, and is associated with worse kidney damage [ 10 ]. Chemical components, molecular weights, and colloid concentration might expose the human body to different levels of hazards [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Starch macromolecule accumulation also impairs glomerular filtration and is associated with a higher risk of acute renal failure than gelatin [ 7 ]; however, gelatin is associated with a higher incidence of anaphylactic shock [ 8 , 9 ]. Compared to iso-oncotic albumin, hyperoncotic albumin leads to a higher osmotic pressure, which may alter intraglomerular oncotic force and osmotic nephrosis, and is associated with worse kidney damage [ 10 ]. Chemical components, molecular weights, and colloid concentration might expose the human body to different levels of hazards [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kidney damage caused by endotoxin [18] is particularly sensitive to venous congestion. In this context, uid overload can result in severe and sustained kidney injury [38].…”
Section: Discussionmentioning
confidence: 99%
“…Histological ndings were graded from 0 to 4 (0, no change; 1, changes affecting 25% of the eld of view; 2, changes affecting 25-50%; 3, changes affecting 51-75%, and 4, changes affecting >75% of the eld), according to the area affected by the features of interest (edema, tubular cell vacuolization, deranged brush border in proximal tubular epithelia, tubular cell death/desquamation, and in ammation). The nal kidney injury score in each rat was expressed as the sum of all values of all features obtained and ranged from 0 to 20 [18].…”
Section: Acute Kidney Injury Scorementioning
confidence: 99%
“…3a). In experimental ARDS, both iso-(4%) and hyper-oncotic (20%) human albumin preserved the integrity of the endothelial barrier compared to Ringer lactate [63], in a mechanism apparently mediated by reduced lung inflammation [64].…”
Section: Albumin In Ardsmentioning
confidence: 99%
“…Neutrophil-mediated epithelial injury has been associated with multiple mechanisms: tumor necrosis factor (TNF)-α, neutrophil extracellular traps (NETs), and TNF-related apoptosis-inducing ligand (TRAIL) [65,66]. In preclinical ARDS studies, albumin attenuated lung damage by reducing oxidative stress and pulmonary inflammation [38,39,63]. However, in vitro [67] and in vivo [68] studies reported that hyper-oncotic albumin (20-25%) was associated with renal dysfunction proportional to its concentration.…”
Section: Albumin In Ardsmentioning
confidence: 99%